Re: Agrawal et al. Ultra-mini-percutaneous nephrolithotomy: A minimally-invasive option for percutaneous stone removal - Kamarulzaman, Mohd Nazli (Medknow, 2017)
The authors demonstrate a successful reduction in size from 30F for conventional PCNL to 11F in ultra-mini-PCNL. This reduction will reduce tissue trauma and bleeding.[1] Further, they did not routinely use a nephrostomy or stent which will possibly allow us to categorize ultra-mini-PCNL as less invasive than conventional PCNL.